Simplified calculation model for offshore wind tower founded on monopile member. (May 2023) - Campione, Giuseppe
Abstract: The objective of the study, concerning the soil-structure interaction of monopile foundations of wind towers consituted by steel tube with hollow cross-sections, was to determine the structural response of wind tower considering the interaction with the foundation. The study was based on elastic and plastic analyses of monopile foundation. The moment-rotation curves of the soil-foundation complex were determined, to be used in verification of the ultimate and operating limit states. The influence of foundation characteristics and type of soil was considered in the calculus of first frequency and critical length. Finally, an experimental validation of the proposed model was made with the data available from the literature in terms of both first frequency and moment rotation response.